THE COMPUTERIZATION OF PLANNING AND ACCOUNTING SYSTEM OF THE IMPLEMENTATION PLAN FOR THE RAILWAY DEPARTMENT - Zenchuk, M. F. (Science and Transport Progress, 2008)
Opportunities of development and application of the specialized software for computerization of planning process on branches of the railway are considered. Features of development of the plans, requirements to the software and principles of its operation are also considered.